A cross-syndrome evaluation of a new attention rating scale: The Scale of Attention in Intellectual Disability. (October 2016) - Freeman, Nerelie C.; Gray, Kylie M.; Taffe, John R.; Cornish, Kim M.
Highlights: ADHD symptoms may present differently in children with intellectual disability (ID) compared with typically developing children. This study uses a newly developed teacher rating scale, the Scale of Attention in Intellectual Disability, to assess ADHD symptoms in children with ID. This study compared ADHD symptoms in children with autism spectrum disorder (ASD), Down Syndrome (DS) and idiopathic intellectual disability. Children with ASD displayed a greater breath of hyperactive/impulsive behaviours than children with DS or idiopathic ID. Abstract: Whilst neuropsychological research has enhanced our understanding of inattentive and hyperactive behaviours among children with intellectual disability (ID), the absence of rating scales developed for this group continues to be a gap in knowledge. This study examined these behaviours in 176 children with autism spectrum disorder (ASD), Down Syndrome (DS), or idiopathic ID using a newly developed teacher rating scale, the Scale of Attention in Intellectual Disability. Findings suggested that children with ASD had a significantly greater breadth of hyperactive/impulsive behaviours than those with DS or idiopathic ID. These findings support existing research suggesting differing profiles of attention and activity across groups. Understanding disorder-specific profiles has implications for developing strategies to support students with ID in the classroom.